Comparative study of FNAC and histopathology of thyroid swellings, diagnostic accuracy and role in its management - Kumar, Abhay; Bhadouriya, Sunil Kumar Singh; Narain, Prem; Chauhan, Jitendra Pratap Singh; Bharti, Bhartendu; Singh, Jaypal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Even if non-surgical and non-invasive techniques can provide a diagnosis, the ultimate answer rests in the histopathological examination of the excised thyroid tissue. This study was carried out with the objective of comparing the findings of the two tests namely FNAC and HPE and suggestions for the future. Methods: This two year prospective study involved 295 outdoor cases with thyroid lesions at UPRIMS & R, Saifai, Etawah, U.P. The preoperative FNAC and postoperative histopathology reports were correlated and conclusions drawn after statistical analysis. Results: More than half (65.4% cases) the number of thyroid FNACs were diagnosed as colloid goitre. Diagnostic categorization of 295 thyroid FNACs based on Bathesda classification showed that 239 (81.01%) cases were cytologically benign, 2 cases (0.68 %) were under atypia of undetermined significance (AUS) while six cases (2.03%) under the neoplasm category- follicular. Suspicious for malignancy category included two cases (0.68%)- hyalinizing trabecular adenoma/columnar variant of papillary carcinoma and medullary carcinoma/oncocytic neoplasm. Under the malignant category, there were fourteen cases (4.05%) cytologically diagnosed and in the inadequate/non-diagnostic category there were 32 cases (10.85%) of cases. Conclusions: FNAC is a simple, safe and cost effective modality in investigation of thyroid disease with high accuracy and specificity.